The Maternal Microbiome Programs the m6A Epitranscriptome of the Mouse Fetal Brain and Intestine - Xiao, Zhuoyu; Liu, Sun; Li, Zengguang; Cui, Jinru; Wang, Hailan; Wang, Zihan; Ren, Qihuan; Xia, Laixin; Wang, Zhijian; Li, Yuan (Frontiers in Cell and Developmental Biology, 2022)
The microbiome exerts profound effects on fetal development and health, yet the mechanisms underlying remains elusive. N6-methyladenosine (m6A) plays important roles in developmental regulation. While it has been shown that the microbiome affects the mRNA m6A modification of the host, it remains unclear whether the maternal microbiome affects m6A epitranscriptome of fetus so as to impact fetal development. Here, we found that loss of the maternal microbiome altered the expression of m6A writers and erasers, as well as the m6A methylome of mouse fetal brain and intestine on embryonic day 18. From the m6A profiles, we identified 2655 and 2252 m6A modifications regulated by the maternal microbiome in fetal brain and intestine, respectively, and we demonstrated that these m6A-modified genes were enriched in the neuro/intestinal developmental pathways, such as the Wnt signaling pathway. The expression of the m6A-modified genes was also altered subsequently. Finally, we verified that antibiotic treatment mostly recapitulated changes in m6A and in the expression of developmental genes, and we further showed that the loss of heterozygosity of Mettl3 rescued m6A levels and the expression changes of some developmental genes in the fetal intestine that resulted from antibiotic treatment. Collectively, our data revealed that the maternal microbiome programs the m6A epitranscriptome of mouse fetal brain and intestine, and regulates subsequent developmental gene expression.